Overview of carbon nanostructures and nanocomposites for electromagnetic wave shielding. (December 2018) - Wang, Chao; Murugadoss, Vignesh; Kong, Jie; He, Zhenfeng; Mai, Xianmin; Shao, Qian; Chen, Yanjun; Guo, Li; Liu, Chuntai; Angaiah, Subramania; Guo, Zhanhu
Abstract: Based on the contributions of carbon nanostructures and their composited species, great advances in electromagnetic wave interference shielding have been achieved. In this article, recent progress in electromagnetic wave shielding enabled by the synergism of carbon nanostructures and their corresponding composites is discussed encompassing the factors of microstructural defects, filler concentration, filler alignment, filler inherent conductivity and the surrounding temperature. Carbon nanostructures and their composites would energize the advanced electromagnetic wave shielding because of their light weight, high corrosion resistance, excellent thermal, mechanical, and electrical properties, broad absorption frequency bandwidth and cost-effectiveness. In this context of identifying suitable carbon composites that can enhance electromagnetic wave absorption. This review provides updated electromagnetic wave shielding knowledge of carbon nanostructures and their composites as well as their prospects and challenges. Graphical abstract: Image